A preliminary study for the production of high specific activity radionuclides for nuclear medicine obtained with the isotope separation on line technique. (September 2017) - Borgna, F.; Ballan, M.; Corradetti, S.; Vettorato, E.; Monetti, A.; Rossignoli, M.; Manzolaro, M.; Scarpa, D.; Mazzi, U.; Realdon, N.; Andrighetto, A.
Abstract: Radiopharmaceuticals represent a fundamental tool for nuclear medicine procedures, both for diagnostic and therapeutic purposes. The present work aims to explore the Isotope Separation On-Line (ISOL) technique for the production of carrier-free radionuclides for nuclear medicine at SPES, a nuclear physics facility under construction at INFN-LNL. Stable ion beams of strontium, yttrium and iodine were produced using the SPES test bench (Front-End) to simulate the production of 89 Sr, 90 Y, 125 I and 131 I and collected with good efficiency on suitable targets. Highlights: The use of ISOL method for radionuclides production is proposed. ISOL method allows to produce carrier-free radionuclides for nuclear medicine. Tests with stable ion beams were produced as a proof of concept. Sodium Chloride is suitable as material for targets for Sr and Y beams. Activated Carbon can be compacted with PVA to have a solid target for I2 beams.